A Lightweight Authentication and Key Management Scheme for Wireless Sensor Networks. (19th October 2016) - Qin, Danyang; Jia, Shuang; Yang, Songxiang; Wang, Erfu; Ding, Qun
Abstract : Security problem is one of the most popular research fields in wireless sensor networks for both the application requirement and the resource-constrained essence. An effective and lightweight Authentication and Key Management Scheme (AKMS) is proposed in this paper to solve the problem of malicious nodes occurring in the process of networking and to offer a high level of security with low cost. For the condition that the mobile sensor nodes need to be authenticated, the keys in AKMS will be dynamically generated and adopted for security protection. Even when the keys are being compromised or captured, the attackers can neither use the previous keys nor misuse the authenticated nodes to cheat. Simulation results show that the proposed scheme provides more efficient security with less energy consumption for wireless sensor networks especially with mobile sensors.